BANCR Regulates The Cell Invasion And Migration In Esophageal Squamous Cell Carcinoma Through Wnt/β-Catenin Signaling Pathway - Chen, Quan (Onco Targets Ther, 2019)
OBJECTIVE: To explore the regulation of long-chain noncoding BANCR on cell invasion and migration of esophageal squamous carcinoma cells and related mechanisms. METHOD: The mRNA expression of BANCR in esophageal squamous carcinoma cells and esophageal squamous cells was detected by quantitative PCR . The relationship between the expression of BANCR and the survival rate of patients with esophageal squamous cell carcinoma (ESCC) was analyzed by Kaplan–Meier method. The BANCR pair was detected by Transwell invasion and scratch test. In ESCC cell lines, the cells had invasion and migration ability; Western blot was applied to detect the expression of proteins involved in the Wnt/β-catenin signaling pathway. RESULTS: BANCR revealed relatively high expression in esophageal squamous carcinoma cells, and the higher the expression of BANCR was, the lower the survival rate of patients with ESCC was. Inhibition of BANCR expression could effectively reduce the invasion and migration ability of esophageal squamous cell carcinoma. After silencing BANCR, the expression of wnt3a, survivin, β-catenin and c-myc protein was downregulated compared with the negative control group (p<0.05). CONCLUSION: Long-chain noncoding BANCR was highly expressed in patients with ESCC and was negatively correlated with patients' survival time. It was of the capability to modulate the cell migration and invasion of ESCC cells through inducing Wnt/β-catenin signaling pathway.